1998
DOI: 10.1046/j.1365-8711.1998.01940.x
|View full text |Cite
|
Sign up to set email alerts
|

Star formation in southern Seyfert galaxies

Abstract: We have produced radio maps, using the ATCA, of the central regions of six southern Seyfert 2 galaxies (NGC 1365, 4945, 6221, 6810, 7582, and Circinus) with circumnuclear star formation, to estimate the relative contribution of star formation activity compared to activity from the active galactic nucleus (AGN). The radio morphologies range from extended diffuse structures to compact nuclear emission, with no evidence, even in the relatively compact sources, for synchrotron self-absorption. In each case the rad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 29 publications
(38 reference statements)
9
43
0
Order By: Relevance
“…Strickland (2007) concluded that NGC 6810 is in fact a "full disk" superwind galaxy and that the previous classification is based largely on misidentification of counterparts in a low resolution radio survey and the merged line profiles of an outflowing wind. This is compatible with the earlier observation (Forbes & Norris 1998) that the radio, FIR, and [Fe ii] properties of the inner disk are ) shows striking evidence for an "ionization cone" on the near side of the disk. These structures are not unique to AGN sources (e.g., Pogge & Eskridge 1987;Tadhunter & Tsvetanov 1989) having been observed in starburst galaxies (e.g., Shopbell & Bland-Hawthorn 1998).…”
Section: Ngc 6810supporting
confidence: 92%
See 1 more Smart Citation
“…Strickland (2007) concluded that NGC 6810 is in fact a "full disk" superwind galaxy and that the previous classification is based largely on misidentification of counterparts in a low resolution radio survey and the merged line profiles of an outflowing wind. This is compatible with the earlier observation (Forbes & Norris 1998) that the radio, FIR, and [Fe ii] properties of the inner disk are ) shows striking evidence for an "ionization cone" on the near side of the disk. These structures are not unique to AGN sources (e.g., Pogge & Eskridge 1987;Tadhunter & Tsvetanov 1989) having been observed in starburst galaxies (e.g., Shopbell & Bland-Hawthorn 1998).…”
Section: Ngc 6810supporting
confidence: 92%
“…Sandqvist et al 1995). The radio/far-IR ratio is also indicative of a dominant circumnuclear starburst (Forbes & Norris 1998). The extended ionized gas in NGC 1365 has been extensively studied with long-slit spectroscopy.…”
Section: Agn 321 Ngc 1365mentioning
confidence: 99%
“…Radio continuum observations of NGC 1365 using the ATCA have been presented by Forbes & Norris (1998). Radio maps were obtained at 3 and 6 cm giving an effective resolution of ∼1 arcsec and ∼2 arcsec respectively.…”
Section: Radio Observations Of Ngc 1365mentioning
confidence: 99%
“…The cone is also aligned with a suggested radio jet (Sandqvist, Jörsäter & Lindblad 1995), although we shall discuss the nature of this jet in more detail later. Radio observations of NGC 1365 by Saikia et al (1994), Sandqvist et al (1995) and Forbes & Norris (1998) reveal a complex, possibly ring‐like structure around the nucleus, but with several radio hotspots loosely coincident with the giant H II regions.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation